The Sentence Fallacies in the Narrative Writing: A Descriptive Study of Gender Differences at Senior High School - Siti Sundari; Annisa Nur Aurin; Made Adi Andayani T. (EFL Education Journal, 2021)
Writing is one of the important skills that should be mastered by the students. Unfortunately, most of the students still have problems in writing especially in writing good sentences. Problems occur when the sentence form is incorrect. This research was intended to describe the tenth grade students’ sentence fallacies in their narrative writingsand explore the gender differences in their writing products based on the sentence fallacies. The sentence fallacies focused on sentence fragments, comma splices, and run-on sentences. There were 14 male students’ writings and 14 female students’ writings investigated in this research. A descriptive analysis was used to describe the students’ sentence fallacies and the percentage of male and female students’ sentence fallacies. Based on the result of the data analysis, it was found that both male and female students made the three kinds of sentence fallacies in their narrative writings. However, the male students made less sentence fallacies in almost all kinds of sentence fallacies, except in comma splice. The male students made more comma splices compared to the female students.